PC user's bible - Ross, John (Wiley, 2007)
If you want to get the most out of your PC, you've come to the right source. This one-stop reference-tutorial is what you need to succeed with your Windows Vista or Windows XP computer, whether it's a desktop or a laptop. From setting up your PC to using it for games and multimedia to keeping it running smoothly, this comprehensive guide explains it all with clear, step-by-step instructions, tips from power users, and much more. Keep this valuable book on hand and power up with confidence!